Impact of high hydrostatic pressure on the cytokine profile and head and neck cancer cell behavior: implications for oncological safety - Brach, Julia Kristin; Freiin Grote, Vivica; Strüder, Daniel; Kalle, Friederike; Jonitz-Heincke, Anika; Bader, Rainer; Hoffmann, Marco; Scherzad, Agmal; Wirth, Markus; Hackenberg, Stephan (Frontiers in Immunology, 2025)
IntroductionThe devitalization of tissue using high hydrostatic pressure (HHP) is an advanced method for processing tumor-infiltrated cartilage to treat tissue defects. This approach preserves the structural and biomechanical properties of the graft while effectively eliminating tumor cells. However, HHP induces the release of cytokines, which may influence the behavior of residual tumor cells in the surrounding tissue. This study characterizes cytokine profiles of HHP-treated head and neck squamous cell carcinoma (HNSCC) cell lines and evaluated its biological effects on intact tumor cells to further assess the oncological safety of the method.Methods and resultsHHP- treatment resulted in a dose-dependent release of pro-inflammatory cytokines, primarily IL-1α and IL-1β, in all investigated cell lines, while IL-6 and IL-8 concentrations were higher in untreated samples. Functional assays demonstrated that supernatants from HHP-treated HNSCC cells significantly enhanced proliferation, migration, and invasion of HNSCC cells relative to control conditions, with these effects being most pronounced at 200 MPa, a pressure associated with incomplete tumor cell devitalization. At 300 MPa, HHP achieved complete devitalization, correlating with intensified necrotic processes and increased intracellular cytokine release.DiscussionOur findings indicate that while HHP significantly influences the cytokine profile and tumor cell behavior, pressures of ≥300 MPa ensure complete tumor cell devitalization, supporting its oncological safety for clinical applications. Further in vivo studies are needed to validate these observations and confirm the clinical safety of HHP-treated materials.